The Development Of E-Tefl (Eepis Test Of English As A Foreign Language) With Web And Android-Based Simulation At Politeknik Elektronika Negeri Surabaya - Irwan Sumarsono; Eny Kusumawati; Radina Anggun Nurisma (Universitas Islam Madura, 2018)
English is one of the essential factors to gain access to global information and knowledge of science and technology. The rapid expansion of technological education and knowledge in developing countries, such as Indonesia, calls for the need into foreign language proficiency, especially English to meet the demand of global market. Seeing the current challenges of global competition, many higher education institutions set the graduation requirements by assigning the students to follow TOEFL (Test of English as a Foreign Language) in order to measure and determine the capability or proficiency in English-speaking graduates. Considering TOEFL as one of the most ideal test in assessing English skill, this study aims to generate product in the form of E-TEFL (EEPIS Test of English as a Foreign Language) which is established as an evaluation tool to meet the academic needs in Electronic Engineering Polytechnic Institute of Surabaya (PENS). Research and development (R&D) is a method used in this study. The study was conducted through several stages namely (1) need analysis, (2) System design, (3) E-TEFLdevelopment, (4) expert validation (lecturers) and first revision, (5) try-out, (6) final revision. The use of technology in developing E-TEFL application is expected to give another alternative in learning TOEFL and E-TEFL can be used as an ideal assessment tool for proving students’ language proficiency as graduation requirement. Abstrak Bahasa Ingris adalah salah satu faktor penting dalam meraih informasi, pengetahuan an teknologi. perkembangan yrknolgi pendidikan dan ilmu pengetahuan yang cepat di negara berkembang seperti Indonesia, kemampuan bahasa asing, khususnya bahasa Inggris sangat dibutuhkan untuk bisa memenuhi kebutuhan pasar global. Melihat tantangan ini, banyak lembaga pendidikan tinggi menerapkan TOEFL sebagai salah satu syarat kelulusan mahasiswanya. Mengingat TOEFL merupakan salah satu tes yang paling ideal dalam mengukur kemampuan bahasa Inggris, studi ini bertujuan untuk menghasilkan sebuah produk yang berbentuk E-TEFL (EEPIS Test of English as a Foreign Language) yang digunakan sebagai alat evaluasi untuk memenuhi tuntutan akademik. Studi ini menggunakan metode Research and Development melalui beberapa tahapan yaitu, analisa, desain, pengembangan, validasi, revisi, uji coba, dan revisi akhir. Penggunaan teknologi dalam pengembangan apilkasi E-TEFL ini diharapkan bisa digunakan sebagai alat pengukuran kemampuan bahasa Inggris mahasiswa yang ideal